Bone Metastasis Disease from Mucinous Carcinoma of the Breast: A Rare Case Report with Immunohistochemical Confirmation - Hera Novianti; Pamelia Mayorita; Meta Zulyati Oktora; Ataya Hafizhah; Almu Muhammad (Scientific Journal, 2025)
Background: Mucinous carcinoma of the breast (MCB) is a rare histological subtype of invasive breast cancer, comprising 1-7% of all breast carcinomas. It is generally associated with a favorable prognosis due to its indolent course and low metastatic potential. However, distant metastases, including to the bone, are exceptionally rare and pose diagnostic and therapeutic challenges. Case Presentation: We present a case of a 64-year-old woman with a history of MCB who developed progressive back pain and lower limb weakness. MRI showed multiple osteolytic lesions with spinal cord compression. A CT-guided biopsy confirmed metastatic mucinous carcinoma, and immunohistochemical (IHC) staining demonstrated GATA3 positivity, confirming breast origin. The patient received denosumab, aromatase inhibitors, and palliative radiotherapy. Conclusion: This case highlights the importance of considering bone metastases in patients with a history of MCB presenting with skeletal-related events. IHC, particularly GATA3, is crucial in confirming the metastatic origin and guiding targeted treatment strategies.